Is hysterectomy associated with kidney cancer risk? A meta-analysis of cohort studies - Yu, Ling; Yu, Pengkui; Lu, Yi (Frontiers in Oncology, 2023)
Emerging evidence have suggested a potential relationship between hysterectomy and risk of kidney cancer with inconsistent results. We aimed to investigate the association of hysterectomy with kidney cancer risk based on a meta-analysis of all available cohort studies. A comprehensive literature search was performed in the PubMed and Embase database, covering all the papers published by September 2022. The pooled relative risks (RRs) and 95% confidence intervals (CIs) were estimated using a DerSimonian and Laird random effects model. Overall, our meta-analysis included 10 cohorts from 9 studies with approximately 240 million participants. The pooled RR with its 95% CI showed a significantly positive association between hysterectomy and risk of kidney cancer (RR 1.30, 95% CI 1.19-1.41). No obvious heterogeneity was observed across the studies (P = 0.206 for heterogeneity; I2 = 25.9%). In conclusion, findings from this meta-analysis of cohort studies indicated that hysterectomy was positively associated with subsequent kidney cancer risk. Further large prospective studies with long-term follow-up are warranted to verify these findings.